Eficácia de três medicamentos no controle da infecção experimental por Trypanosoma evansi em ratos (Rattus norvegicus) linhagem Wistar - Doyle, Rovaina Laureano (2006)
This paper aimed to describe some lab and histological findings from an experimental infection of Trypanosoma (Trypanozoon) evansi Steel, 1885 (Balbiani, 1888) in rats (Rattus novergicus) belonging to the Wistar strain, testing the effectiveness of three medications. These animals were divided in 4 groups of 10 each and treated to three different chemical treatments after the detection of more than eight tripomastigotes for visual side of the blood smears at the light microscope with 1000 increase. Was tested injectable oxytetracycline 10%, benzonidazol per oss and injectable diminazene 7% while one infected and untreated group remained as control. Evaluation of treatment efficacy was performed through daily blood smears stained by Panotico Rápido® for 60 days. The rats were necropsied aiming histological examination. Treatment with diminazene was the most efficient since no parasites having significant difference (p < 0.05) between males and females of that group, which presented survive after the treatment of 14,4 days more than the males. Histological alterations findings were not specific.